Implementasi program pengembangan kewirausahaan di SDIT Al Madinah Bogor - Darwis, Adnan; Tamam, Abas Mansur; Sastra, Ahmad (Program Studi Magister Pendidikan Islam,Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2024)
This study aims to see the portrait of the entrepreneurial spirit-based life skills education program at SDIT Al Madinah as a form of implementation of personal, social, academic and vocational skills. This entrepreneurial spirit is needed with the habit of living independently and practicing finding solutions to problems faced. This paper uses qualitative, descriptive and field research methods, while the study conducted is a literature study with qualitative descriptive data analysis techniques to obtain a detailed picture of the program. The data used are secondary data from the results of program evaluations at schools, combined with program implementation data. The results of this study are an evaluation of the entrepreneurial spirit-based Life Skills Education program which is held in the form of cultivation activities and integrated with Islamic values according to the sunnah of the Prophet. Its implementation is oriented towards empowering participants and focuses on improving competencies in the form of knowledge, skills and attitudes. This program has been implemented in agricultural (agricultural), fisheries and livestock cultivation activities, with various types of plants and animals that can be developed and have economic value, as well as being a learning process for children in building and developing an Islamic entrepreneurial spirit. Abstrak Penelitian ini bertujuan untuk melihat potret program pendidikan kecakapan hidup berbasis jiwa kewirausahaan di SDIT Al Madinah sebagai bentuk implementasi kecakapan personal, sosial, akademik dan vokasi. Jiwa kewirausahaan ini dibutuhkan dengan pembiasaaan diri untuk hidup mandiri dan berlatih mencari solusi dari permasalahan yang dihadapi. Tulisan ini menggunakan metode penelitian kualitatif, deskriptif dan field research, sementara studi yang dilakukan adalah studi kepustakaan dengan teknis analisis data deskriptif kualitatif untuk mendapatkan gambaran program secara mendetail. Data yang digunakan adalah data sekunder yang berasal hasil evaluasi program di sekolah, digabungkan dengan data implementasi program. Hasil dari studi ini adalah evaluasi program Pendidikan Kecakapan Hidup berbasis jiwa kewirausahaan yang diselenggarakan dalam bentuk kegiatan budidaya dan diintegrasikan dengan nilai-nilai keislaman sesuai sunah Rasulullah. Pengimplementasiannya berorientasi pada pemberdayaan peserta dan terfokus pada peningkatan kompetensi berupa pengetahuan (knowledge), keterampilan (skill) dan sikap (attitude). Program ini telah diimplementasikan pada kegiatan budidaya agrikultur (pertanian), perikanan dan peternakan, dengan beragam jenis tanaman dan hewan yang bisa dikembangkan dan bernilai ekonomis, sekaligus menjadi proses pembelajaran anak dalam membangun dan mengembangkan jiwa wirausaha secara Islami.